Haemodialysis impairs clopidogrel but not aspirin responsiveness in patients with end-stage renal disease - Htun, Patrik; Kan, Tatiana; Mueller, Eda; Pohle, Cosima; Schindler, Ralf; Geisler, Tobias; Gawaz, Meinrad; Bocksch, Wolfgang; Fateh-Moghadam, Suzanne (Thrombosis and Haemostasis, 2014)
Dual antiplatelet therapy (DAPT) with aspirin (ASA) and clopidogrel (Clp) is the standard treatment to reduce ischaemic coronary events, but in patients with end-stage renal disease (ESRD) the efficacy of Clp remains unclear. Patients with ESRD are at higher risk for coronary artery disease (CAD) and also their post-interventional outcome is worse compared to patients with normal renal function. Little is known about the influence of haemodialysis (HD) on ASA and Clp responsiveness. To assess the effect of HD on ASA- and Clp-responsiveness in patients with documented CAD and ESRD, 31 patients with ESRD (mean age 66.5 ± 1.8 years, 23 male ) on DAPT were evaluated for their ASA and Clp responsiveness with the Verify Now System (Accumetrics Inc.) We measured the antiplatelet effect in all ESRD patients at three time points: T1: just before HD; T2: directly after HD; T3: steady state on a HD free day one week after T1. In our study at baseline 10 (32.3%) patients were ASA-low responder (ASA-LR) and 14 (45.2%) patients Clp-low responder (Clp-LR). There was a significant difference in the PRU values before ( T1) and immediately after HD (T2) [PRU T1=234 (169; 274) vs PRUT2= 247 (199; 278); pT1,2=0.036; ]. Results were shown as median ARU T1 (25th, 75th percentile) or median PRU T1 (25th, 75th percentile). Hence HD seems to impair responsiveness to Clp, resulting in an increase of 6.5 % Clp-LR. No significant differences in the ARU values at the different time-points were found.
Keywords: Aspirin low responder; clopidogrel low responder; end stage renal disease; haemodialysis; antiplatelet therapy